ANALISIS SISTEM PENGENDALIAN INTERNAL SIKLUS PENJUALAN DAN PIUTANG USAHA (STUDI KASUS PT. RASA PRIMA SELARAS) - Lidiya Paramita; Leriza Desitama Anggraini; Rafika Sari (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
This study aims to determine whether the Standard Operating Procedure (SOP) on the sales cycle and accounts receivable has been implemented by PT. Rasa Prima Selaras and know how to implement the internal control system in the sales cycle and accounts receivable of PT. Rasa Prima Selaras and know the level of effectiveness and efficiency of the internal control system sales cycle and accounts receivable at PT. Rasa Prima Selaras on the cycle of sales and accounts receivable of PT. Prima Taste Harmonizes. So that it can indicate and provide recommendations on the weaknesses contained in the sales cycle and accounts receivable. The object of this research is all parts related to the function cycle of sales and receivables at PT. Rasa Prima Selaras which is engaged in the cimory distributor business. This study uses a descriptive method and the data used are primary data and secondary data. Data collection techniques used include: literature study, observation, interviews, questionnaire checklists, and documentation. The results of this study concluded that the cycle of sales and accounts receivable at PT. Rasa Prima Selaras has been implemented quite in accordance with the applicable Standard Operating Procedure (SOP), but there are still many things that have not been implemented in accordance with the applicable SOP. And also the internal control system for the sales cycle and accounts receivable at the company is considered quite effective and efficient, but there are still some weaknesses in the control that the company can still evaluate.